Análise da evolução da pobreza no nordeste brasileiro e no estado da Paraíba no período 1995-2009 - Araújo, Sabrina Martins de (2012)
The main purpose of this study is to analyze the poverty evolution on Northeast and on Paraíba at the period 1995-2009 and sub-periods 1995-2002 and 2003-2009. For this, we used secondary data on monthly household income and per capita personal income from all sources, obtained from IBGE´s PNAD. The poverty evolution study was performed using the FGT poverty measures group and poverty decomposition techniques for economic activity, a method developed by Ravallion and Huppi (1990, 1991) and between components growth and income redistribution developed by Datt and Ravallion (1991). In addition, we performed a study on its determinants using, for this, a logit model. The results showed that the reduction in poverty over the studied periods, except the proportion of poor people in Paraíba which increased at the subperiod 1995-2002; that the activity sectors with greatest contribution to poverty reduction are: agriculture, public administration, manufacturing, trade and repair and construction; that, in general, the changes in poverty within activities sectors (intra-sectoral effect) contributed more to poverty reduction than the aggregated population displacement between these sectors (effect inter-sectoral); that, in most cases, economic growth was the factor that most contributed to poverty reduction; and that from the econometric model, it was found that being female, being busy in agriculture and reside in the rural area, increases the chances of an individual being poor; that as age increases, the chances of being poor decreases, but from a certain point tends to rise, showing the effects of the life cycle; that education has a strong influence on the condition of poverty, given that the higher the education level is the less is the chance to be poor, on the other hand the variables of location and color showed some adverse results, and in most cases not significant.